Suppose {$a_n$} be a sequence of posetive real numbers such that $a_n\ge a_{n+1}$ for all $n\ge1$ and $\sum_{n=1}^{\infty}a_n <\infty$ then which of the following(s) is true:

A. $\lim_{n\to \infty}a_n=0$

B.$\lim_{n\to \infty}na_n=0$

C.$\lim_{n\to \infty}n^2a_n=0$


As the corresponding series convergent so nth term of the series goes to 0. So A is correct.If $a_n=1/n^2$ then C can be removed. I can not understand about other options. Please help.

  • $\begingroup$ Are there multiple right answers, or is there a single correct answer? $\endgroup$ – Demetri Pananos Feb 27 '15 at 7:50
  • 2
    $\begingroup$ @DemetriP: Several of them are true. $\endgroup$ – Regret Feb 27 '15 at 7:51
  • $\begingroup$ C) is false, but your reasoning can be stronger. Try using the ratio test. I'm still thinking about the others. $\endgroup$ – Demetri Pananos Feb 27 '15 at 7:57

B and D are also true. Let $s_n$ be the sequence of partial sums of $\sum_{n = 1}^\infty a_n$. Then

$$(1)\qquad s_{2n} - s_n = a_{n+1} + \cdots + a_{2n} \ge na_{2n}$$

and $$(2) \qquad s_{2n+1} - s_n = a_{n+1} + \cdots + a_{2n+1} \ge (2n+1)a_{2n+1}.$$

Since $s_n$ converges, $(1)$ implies $2na_{2n} \to 0$, and $(2)$ implies $(2n+1)a_{2n+1} \to 0$. Therefore $na_n \to 0$ and B holds.

Since $\sum_{n = 1}^\infty a_n$, given $\epsilon > 0$, there exists a positive integer $N$ such that $|A - s_n| < \epsilon$ for all $n \ge N$. This implies $$\left|\sum_{m = n}^\infty a_m\right| < \epsilon$$ for all $n > N$. Since $\epsilon$ was arbitary, D follows.

  • A. True

Classicaly, if $\sum_{n}a_n$ converges, then $a_n\to 0$

  • B. True

Let $n\in \mathbb N$. Then $2na_{2n}\leq 2(a_{2n}+\ldots+a_{n+1})=S_{2n}-S_n$ where $S_n$ the n-th partial sum.

Since $\sum_{n} a_n$ converges, $\lim_{n\to\infty} S_{2n}-S_n =0$.

Hence $\lim_{n\to\infty}2na_{2n}=0$

Moreover $(2n+1)a_{2n+1}=2na_{2n+1}+a{2n+1}\leq 2na_{2n}+a_{2n+1}$

Hence $\lim_{n\to\infty}(2n+1)a_{2n+1}=0$

Hence $\lim_{n\to\infty} na_n=0$

  • D. True

Classically, writing $\sum_{m=n}^\infty a_m = \sum_{m=1}^\infty a_m - \sum_{m=1}^{n-1}a_m$ and recalling that, as a sequence, $\lim_{n\to\infty}\sum_{m=1}^{n-1}a_m=\sum_{m=1}^\infty a_m$ yields the result.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.